Event Ethnography: A Modern Approach to Anthropological Research and Writing about Christmas - Lidija Radulović (University of Belgrade, 2016)
"Event Ethnography": A Modern Approach to Anthropological Research and Writing about Christmas. Review of the book by Vesna Vučinić-Nešković,  Christmas in Boka Kotorska: anthropological essays of public firings of the Yule log in the time of post socialism. The Faculty of Philosophy, University of Belgrade and "Čigoja publishing". Belgrade 2008. 357 pages.